Buying into change : mass consumption, dictatorship, and democratization in Franco's Spain, 1939-1982 - Gómez del Moral, Alejandro J. (University of Nebraska Press, 2021)
Buying into Change examines how the development of a mass consumer society under the dictatorship of Generalissimo Francisco Franco (1939-1975) inserted Spain into transnational consumer networks and set the stage for Spain's transition to democracy during the late 1970s.
Keywords: Democratization -- Spain -- History -- 20th century.; Consumers -- Spain -- History -- 20th century.; Consumption (Economics) -- Social aspects -- Spain -- History -- 20th century.; Spain -- Politics and government -- 1975-1982.; Spain -- Politics and government -- 1939-1975.; Démocratisation -- Espagne -- Histoire -- 20e siècle.; Espagne -- Politique et gouvernement -- 1975-1982.; Espagne -- Politique et gouvernement -- 1939-1975.; Consommateurs -- Espagne -- Histoire -- 20e siècle.; Société de consommation -- Aspect social -- Espagne -- Histoire -- 20e siècle.; HISTORY -- Europe -- Spain & Portugal.; Politics and government; Democratization; Consumption (Economics) -- Social aspects; Consumers; Spain; 1900-1999; Electronic books.; History